Corporate governance and financial reporting quality of construction companies in Nigeria - Kaka, Emmanuel John (Journal of Contemporary Accounting, 2023)
This study seeks to examine corporate governance and financial reporting quality of construction companies quoted on the Nigerian Stock Exchange for the period 2016 to 2020. Corporate governance mechanism was proxies by board size, board composition and audit committee composition. Data were collected from annual financial statement of the companies for the study period and analyzed using descriptive statistics, Correlation analysis and Regression analysis by using E-views9 software. The result indicated that board composition and audit committee had positive and significant effect on the financial reporting quality of construction companies. While, board size has a negative and significant effect on financial reporting quality of construction companies. This shows that corporate governance has significant impact on the financial reporting quality of quoted construction companies. The study recommended that strategy need to be developed in order to ensure adherence to corporate governance codes in construction companies, so as to ensure the presentation of articulated, encompassing financial statements.